2008
DOI: 10.1080/10428190802210700
|View full text |Cite
|
Sign up to set email alerts
|

Phase I evaluation of gemcitabine, mitoxantrone, and their effect on plasma disposition of fludarabine in patients with relapsed or refractory acute myeloid leukemia

Abstract: Our aim was to estimate the duration of maximum tolerated dose (MTD) duration for gemcitabine given as a continuous infusion in combination with fludarabine and mitoxantrone and to evaluate potential pharmacokinetic (PK) interactions in 17 patients with refractory or relapsed acute myeloid leukaemia (AML). Gemcitabine was administered at 10 mg/m(2)/min for 3-15 h, fludarabine at 25 mg/m(2) daily for days 1-5 and mitoxantrone at 10 mg/m(2) daily on days 1-3. PK studies revealed that fludarabine clearance was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…38,39 Phase I studies at our institution using a single prolonged infusion gemcitabine in AML has shown promising results. 40,41 In addition, this study led to the exploration of the biology of AML in older adults at a gene-expression level. Our group at Duke was able to demonstrate that older adults with AML have a higher probability of RAS, TNF, and Src pathway activation compared to their younger counterparts.…”
Section: Future Directionsmentioning
confidence: 99%
“…38,39 Phase I studies at our institution using a single prolonged infusion gemcitabine in AML has shown promising results. 40,41 In addition, this study led to the exploration of the biology of AML in older adults at a gene-expression level. Our group at Duke was able to demonstrate that older adults with AML have a higher probability of RAS, TNF, and Src pathway activation compared to their younger counterparts.…”
Section: Future Directionsmentioning
confidence: 99%